2019
DOI: 10.1016/j.cgh.2018.10.041
|View full text |Cite
|
Sign up to set email alerts
|

Time to Colonoscopy and Risk of Colorectal Cancer in Patients With Positive Results From Fecal Immunochemical Tests

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e82. Learning Objective-Upon completion of this activity, successful learners will be able to utilize current evidence to manage patients with positive fecal immunochemical test results for the purpose of colorectal cancer prevention. BACKGROUND & AIMS: In patients with positive results from a fecal immunochemical test (FIT), failure to receive a timely follow-up colonoscopy may be associated with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 18 publications
5
84
0
Order By: Relevance
“…On the other hand, our data indicate that the 3-year survival rate is lower in these patients than those in the screen-detected group (75.6% vs. 93.5%). These data are in line with other studies [37] including that of Corley et al [38], based on a retrospective cohort in California, which observed a higher risk of advanced CRC stages in patients in whom a colonoscopy was performed more than 6 months after a positive FIT. In relation to this, according to the simulation model of Meester et al [39], a delay in diagnosis of more than 12 months after a positive FIT reduces the benefits of screening programmes.…”
Section: Ccr In Fit-positive Patients Who Declined Colonoscopysupporting
confidence: 92%
“…On the other hand, our data indicate that the 3-year survival rate is lower in these patients than those in the screen-detected group (75.6% vs. 93.5%). These data are in line with other studies [37] including that of Corley et al [38], based on a retrospective cohort in California, which observed a higher risk of advanced CRC stages in patients in whom a colonoscopy was performed more than 6 months after a positive FIT. In relation to this, according to the simulation model of Meester et al [39], a delay in diagnosis of more than 12 months after a positive FIT reduces the benefits of screening programmes.…”
Section: Ccr In Fit-positive Patients Who Declined Colonoscopysupporting
confidence: 92%
“…The fact that a time to colonoscopy after FOBT up to 6 months was not associated with any increase in CRC prevalence or in CRC stage progression supports the overall safety of an extended time to colonoscopy after a positive FOBT. Despite the intrinsic limitations of the study by Zorzi et al (a retrospective design with confounding factors that hamper causality deductions, a minority of patients with long delays, and an unknown CRC stage in one-third of cases), the findings are consistent with those of a large study from the USA 7 and another from Asia 8 that have evaluated CRC outcomes associated with variations in follow-up times. According to the report by Corley et al 7 , concerns regarding an increased risk of CRC and late-stage CRC arise about 10 months after a positive FIT result.…”
supporting
confidence: 78%
“…In 2004, Taiwan launched a national colorectal cancer screening program that provided fecal immunochemistry tests (FIT) [ 41 ], and, in 2013, it began subsidizing fecal occult blood tests (FOBT). Biennial regular screenings combined with colonoscopy [ 42 ] are expected to reduce the incidence of colorectal cancer in the future [ 43 ].…”
Section: Discussionmentioning
confidence: 99%